Hump-nosed viper bite: an important but under-recognized cause of systemic envenoming - Shivanthan,Mitrakrishnan Chrishan (2014)
Hump-nosed viper bites are common in the Indian subcontinent. In the past, hump-nosed vipers (Hypnalespecies) were considered moderately venomous snakes whose bites result mainly in local envenoming. However, a variety of severe local effects, hemostatic dysfunction, microangiopathic hemolysis, kidney injury and death have been reported following envenoming byHypnalespecies. We systematically reviewed the medical literature on the epidemiology, toxin profile, diagnosis, and clinical, laboratory and postmortem features of hump-nosed viper envenoming, and highlight the need for development of an effective antivenom.